Alter bei SLE-Diagnose beeinflusst Krankheitsverlauf (Aktuelle Rheumatologie, 2017)
Joo YB et al. Differences in Clinical Features and Mortality between Childhood-onset and Adult-onset Systemic Lupus Erythematosus: A Prospective Single-center Study.